The evolution of virtual identity: a systematic review of avatar customization technologies and their behavioral effects in VR environments - Ouhnni, Hamid; Btissam, Acim; Meryam, Belhiah; El Bouchti, Karim; Seghroucheni Yassine, Zaoui; Lagmiri, Souad Najoua; Rigalma, Benachir; Ziti, Soumia (Frontiers in Virtual Reality, 2025)
Over the past 10 years, advancements in virtual reality (VR) technologies have been profound, yielding significant transformations within the digital milieu. This paper presents an extensive analysis of the cutting-edge research surrounding avatar customization in VR, concentrating on the technologies, methodologies, and challenges pertinent to the creation and management of digital representations. Through a meticulous examination of 45 curated studies, the research investigates three pivotal dimensions: the determinants affecting the aesthetic characteristics of avatars, the progression of avatar creation methodologies, and the practical applications of avatar customization. The investigation emphasizes the critical role of avatar customization in augmenting user identification, social presence, and interaction within virtual environments. Furthermore, it delves into nascent trends in avatar development, including artificial intelligence-driven customization tools and real-time rendering methodologies, which facilitate the production of increasingly realistic and individualized avatars. The concluding section articulates prospective trajectories for innovation within this domain, underscoring opportunities for further inquiry and the formulation of more diverse and adaptable strategies for avatar customization, thereby accommodating users across a spectrum of virtual environments.